FINANCIAL DISTRESS SEBAGAI DETERMINAN, PEMEDIASI DAN PEMODERASI DARI PRAKTIK MANAJEMEN LABA - Felicia Chrisantha; Sugi Suhartono (Jurnal Bina Akuntansi, 2022)
Financial distress is a situation where the company's finances are in an unhealthy or crisis state. Based on agency theory, in a state of financial distress the principal and agent have two different interests in the company in which each party seeks to achieve and maintain the expected level of prosperity. Previous research stated that in a state of financial distress, companies do not always implement earnings management to overcome them. This study aims to determine financial distress as determinant, mediating, and moderating earnings management. The conclusion of this study is that profitability affects financial distress and earnings management, financial distress is able to moderate the negative interaction of firm size on earnings management. However, there is not enough evidence of financial distress as a determination and mediation of earnings management, firm size on financial distress and earnings management, and profitability moderated by financial distress on earnings management.